Loss Aversion, Risk Aversion, and the Shape of the Probability Weighting Function - Matthew D. Rablen (Center for Economic Studies and ifo Institute (CESifo), 2023)
Loss aversion, risk aversion, and the probability weighting function (PWF) are three central concepts in explaining decisionmaking under risk. I examine interlinkages between these concepts in a model of decisionmaking that allows for loss averse/tolerant stochastic reference dependence and optimism/pessimism over probability distributions. I give a preference interpretation to commonly observed shapes of PWF and to risk aversion. In particular, I establish a connection between loss aversion and both risk aversion and the inverse-S PWF: loss aversion is a necessary condition to observe each of these phenomena. The results extend to distinct PWFs in the gain and loss domains, as under prospect theory.
Keywords: D91; D81; D01; 330; probability weighting; rank dependent expected utility; loss aversion; risk aversion; reference dependence; optimism; pessimism; prospect theory